Power management for energy harvesting over LEACH protocol - Alsader, Moner; Savvaris, Al (NAUN.ORG, 2019)
Wireless Sensor Network devices are characterized byresource constraints such as computational power, memory andenergy. Since these devices are powered by batteries, it may not be possible to replace batteries for recharging and therefore, energy harvesting techniques such as Piezoelectric and Thermoelectric can be used if necessary so that the lifetime of these devices canbe extended. This paper presents power management for energy harvesting over LEACH protocol. Experimental results based on the NS-3 simulation platform has shown that Low Energy Adaptive Clustering Hierarchy (LEACH) routing protocol improves the energy efficiency for Piezoelectric energy harvesting in aircraft compared to that of direct simulation
Keywords: WSN; NS-3; Power Management; Energy; LEACH; Piezoelectric